The Houston HeartReach Registry: Recruitment Methods and Current Registry Demographics - Jaqueline Ferrufino, BA; Symone A. Taylor, BSA; Karla Campos, MD; Keri Sprung, MBA; Matthew W. Segar, MD, MS; Stephanie A. Coulter, MD (Texas Heart Institute Journal)
Background: Although Houston, Texas, is a diverse city with opportunities for economic prosperity, many Houston residents have low socioeconomic status and poor access to health care. Cardiovascular disease rates in Houston differ by ethnicity. It is therefore crucial to understand how the risk of cardiovascular disease differs among diverse ethnic and sexual minority populations. Methods: This study assessed the recruitment methods and demographic composition of the Houston HeartReach Registry, a database repository of cardiovascular disease trends and risk factors in Houston's population. The self-reported demographics of the participants recruited to date were analyzed with descriptive statistics. The primary end point of this interim study was the number of women recruited from each location by year, ethnicity, socioeconomic status, health care status, and sexual orientation. The number of women of each ethnicity recruited from each location was also examined. Results: Currently, 1,476 women are enrolled in the registry, including 996 (67.48%) Hispanic women, 233 (15.79%) non-Hispanic White women, 190 (12.87%) Black women, 24 (1.63%) Asian women, and 29 (1.97%) women from other races and ethnicities. Of these 1,476 women, 352 (23.85%) had an annual income of $10,000 to $24,000, 375 (25.41%) had private health insurance, and 342 (23.17%) were heterosexual. Most women enrolled in the registry (1,082 [73.31%]), including most of the Hispanic participants, were recruited at BakerRipley events. Conclusion: To date, 1,476 of a planned 5,000 participants have been enrolled in the Houston HeartReach Registry. At present, Hispanic women make up the majority of participants, indicating an underrepresentation of other ethnic demographics. The enrollment of individuals from sexual minority groups, from varied socioeconomic backgrounds, and with diverse health care statuses aligns proportionally with the total count of recruited women to date. The application of deliberate, culturally nuanced, and demographic-specific recruitment strategies should facilitate the inclusion of desired participants in a comprehensive manner.